2016
DOI: 10.1021/acsphotonics.6b00448
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Lateral Fano Interference Optical Force with Au–Ge2Sb2Te5 Hybrid Nanostructure

Abstract: We numerically demonstrate that a pronounced dipole− quadrupole (DQ) Fano resonance (FR) induced lateral force can be exerted on a dielectric particle 80 nm in radius (R sphere = 80 nm) that is placed 5 nm above an asymmetric bow-tie nanoantenna array based on Au/ Ge 2 Sb 2 Te 5 dual layers. The DQ-FR-induced lateral force achieves a broad tuning range in the mid-infrared region by changing the states of the Ge 2 Sb 2 Te 5 dielectric layer between amorphous and crystalline and in turn pushes the nanoparticle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 70 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…In many cases, such simulations do not provide a physical understanding or intuition of the scenario that could be exploited for future nanosystems. In fact, such physical intuition is highly regarded to unveil hidden symmetries [11][12][13] and understand the consequences of inducing asymmetries in the electrodynamic response of plasmonic nanostructures [14][15][16][17]. This problem can be alleviated by using analytical tools, such as transformation optics [18,19] or its two-dimensional (2D) variant, conformal transformation [19,20], which we have exploited over the last few years [13,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, such simulations do not provide a physical understanding or intuition of the scenario that could be exploited for future nanosystems. In fact, such physical intuition is highly regarded to unveil hidden symmetries [11][12][13] and understand the consequences of inducing asymmetries in the electrodynamic response of plasmonic nanostructures [14][15][16][17]. This problem can be alleviated by using analytical tools, such as transformation optics [18,19] or its two-dimensional (2D) variant, conformal transformation [19,20], which we have exploited over the last few years [13,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…When the GST is tuned between two states, the corresponding permittivity will be changed simultaneously, which can be used to realize active control. Due to its remarkable tuning abilities such as high stability and fast switch speed [29,30], GST has been applied in many novel tunable nano-photonic devices such as multi-wavelength duplex metalens, dipole-quadrupole (DQ) Fano resonance (FR) induced lateral force, beam steering, filter, color control, and ultraviolet/high-energy-visible resonances by combining with metasurfaces [20,[31][32][33][34][35][36], which has proved to be the great potential of GST. Nevertheless, the research for tunable metalens array using phase change materials has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…[52] Unlike other plasmonic tweezers, we found that the DQ-FR in the asymmetric BNAs induces a transverse optical force that pushes the nanoparticles laterally, instead of trapping them. This force switches direction ultrafast by transiting the state of Ge 2 Sb 2 Te 5 , thus providing an opportunity to reversibly control the nanoparticles with plane-wave incident light.…”
Section: Introductionmentioning
confidence: 55%